A COMMUNICATION GUIDE FOR EX-OFFENDERS - Contreras, Richard Anthony (2018)
Incarceration rates and the release rate of ex-offenders into the community are both increasing. Studies have shown, on a consistent basis, that, while incarcerated, ex-offenders experience lower literacy levels than the general population, suffer emotional and mental distress from a harsh prison life, and suffer from the negative effects of public perception. Ex-offender anger abounds. These factors interfere with an inmate’s ability to communicate effectively. Notwithstanding, upon release from custody, how do we help such ex-offenders communicate? Many handbooks exist to help former inmates. However, the vast majority only offer assistance with locating government social services agencies, obtaining documents, and helping with jobs. A few offer help with finding mentors. However virtually none assist with communication techniques. Utilizing clear and simple language, A Communication Guide for Ex-Offenders fills this gap. The guide consists of three sections: the first defines basic concepts of communication, including contextual and cultural aspects. Additionally, it contains information on how ex-offenders can communicate more effectively despite suffering from various mental and emotional issues. Finally, a theoretical application focuses on the importance of disclosing information and making a favorable impression. At the end of each section, there is a review of concepts. This manual will also contain two new features in the application of communication studies and the ex-offender population: A communication ‘Bill of Rights’ for ex-offenders and a pledge on ex-offender responsibilitie